Methods design concept an effective approach for profitability. - Shigeyasu Sakamoto (Journal of the philippine institute of industrial engineers)
A company achieved 1000% increase in profitability with an improvement of around 500% in productivity. One of the factors that lead to the success is the changes made in their approach of methods improvement. That is designing new working methods on white papers rather than analysis of present methods with industrial engineers. I believe, real new and effective methods can be obtained without new appraoch of designing such as MDC.